2021
DOI: 10.3389/fpubh.2020.628789
|View full text |Cite
|
Sign up to set email alerts
|

Clusters in the Spread of the COVID-19 Pandemic: Evidence From the G20 Countries

Abstract: This study tests the validity of the club convergence clustering hypothesis in the G20 countries using four measures of the spread of the COVID-19 pandemic: total number of confirmed cases per million people, new cases per million people, total deaths per million people, and new deaths per million people. The empirical analysis is based on the daily data from March 1, 2020, to October 10, 2020. The results indicate three clusters for the per capita income, two clusters for total cases per million people, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…This underlines the nature of the COVID-19 pandemic and maybe of all pandemics in the past (Spanish flu in 1918) and in future. Meng studied the spread of the COVID-19 pandemic in G20 countries and found that the cases and deaths related to the COVID-19 pandemic had a nonlinear nature and convergence [58]. This means that results about socio-economic, cultural, and population correlates of the effects of the pandemic depend strongly on the sample of countries (e.g., high-income vs low-income) and the phase of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…This underlines the nature of the COVID-19 pandemic and maybe of all pandemics in the past (Spanish flu in 1918) and in future. Meng studied the spread of the COVID-19 pandemic in G20 countries and found that the cases and deaths related to the COVID-19 pandemic had a nonlinear nature and convergence [58]. This means that results about socio-economic, cultural, and population correlates of the effects of the pandemic depend strongly on the sample of countries (e.g., high-income vs low-income) and the phase of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…A 7-day moving average was used to highlight longer-term trends and cycles, as well as to smooth out short-term fluctuations of the data [55]. All data were decomposed into trend and cycle components, using the Hodrick-Prescott filter [56,57].…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, some studies identified patterns of the Covid-19 impact in different countries [4][5][6][7][8]. Other works have used clusters to analyze the Covid-19 impact on counties across the United States [9][10][11].…”
Section: Sociodemographic Factors Associated Withmentioning
confidence: 99%